Development of a Hybrid Training Simulator for Structural Heart Disease Interventions. (1st October 2020) - Jang, Sun-Joo; Torabinia, Matin; Dhrif, Hassen; Caprio, Alexandre; Liu, Jun; Wong, Shing Chiu; Mosadegh, Bobak
Abstract : To address the expanding needs to acquire the necessary skill sets for managing a wide array of transcatheter interventions, a 3D visualization system that integrates into the training platform would significantly enhance the trainee's capacity to comprehend the spatial relationships of various cardiac structures and facilitate the learning process. In addition to procedural training, the same technology may potentially help formulate treatment strategies in preprocedural planning especially in complex anatomy. Herein, a hybrid simulator for structural heart disease interventions is demonstrated by using the combination of a mixed reality (MR) display and 3D printing. The system consists of a 3D printed phantom heart model, a catheter with real‐time tracking using electromagnetic sensors, and the stand‐alone MR display for rendering 3D positions of the catheter within the heart model, along with quantitative feedback. The phantom heart model is generated by 3D printing technology using a segmented geometry from a human cardiac computed tomography (CT) scan. The catheter is coupled with electromagnetic sensors that allow real‐time tracking of their 3D positions and orientations. Custom software and algorithms to coregister and display the catheter's position relative to the phantom heart model are developed to interface with commercial software provided with the tracking sensors and MR display such that updates occur seamlessly in real time. Prespecified target crossings in the fossa ovalis during a transcatheter septal puncture procedure are demonstrated in the training scene. This hybrid training system will be used for training and educating transcatheter septal puncture procedure and other structural heart interventions. Abstract : This article presents a proof‐of‐concept demonstration of a hybrid simulator for cardiac interventions. This hybrid simulator couples a physical 3D printed heart phantom to a mixed reality guidance display. The simulator uses embedded electromagnetic sensors to provide real‐time quantitative feedback of a catheter's position during specific steps of a procedure, based on targets set during preprocedural planning.